Kepemimpinan Pendidikan Perspektif Managemen Mutu Terpadu (Sebagai Upaya Regulasi Mutu Lembaga Pendidikan) - Nanang Budianto (STAIFAS-Press, 2018)
ABSTRACT Leadership leadership must be able to influence, move, guide and maintain people's activities so that organizational goals can be achieved. As expressed by Sudarwan Danim, leadership is the energy that influences and gives direction which is contained in the leader's personal self. Or leadership is energy that can move, guide and maintain people's activities so that organizational goals can be achieved. The same thing was expressed by Owens, leadership is an interaction between one party as the leader with the party led. Keyword : Leadership, Education, Integrated Quality Management